(untitled) (Eurasian Research Bulletin, 2023)
This article analyzes the importance of tourism in economic development, the work being done on the development of the tourism sector in our country. The work on improving the tax administration in the development of the tourism sector has been analyzed. On the basis of legal comparative analyzes of developed foreign countries and advanced experience, a proposal was developed to determine the existing economic problems in the organization of tax administration related to the development of tourism in our country, to develop scientific and practical recommendations related to their solutions, and to improve them.